Boosting the Activity of BaCo0.4Fe0.4Zr0.1Y0.1O3−δ Perovskite for Oxygen Reduction Reactions at Low‐to‐Intermediate Temperatures through Tuning B‐Site Cation Deficiency. Issue 38 (27th August 2019) - Kuai, Xu; Yang, Guangming; Chen, Yubo; Sun, Hainan; Dai, Jie; Song, Yufei; Ran, Ran; Wang, Wei; Zhou, Wei; Shao, Zongping
Abstract: Doped perovskite oxides with the general formula of A x A′1− x B y B′1− y O3 have been extensively exploited as the cathode materials of solid oxide fuel cells (SOFCs), but the performance at low‐to‐medium temperatures still needs improvement. BaCo0.4 Fe0.4 Zr0.1 Y0.1 O3− δ (BCFZY) has been recently reported to show promising oxygen reduction reaction (ORR) activity under SOFCs' operating conditions. Here, it is reported that the activity of BCFZY can be further boosted via introducing a slight B‐site cation deficiency into the oxide lattice, and such an improvement is assigned to an increase in oxygen mobility that brings enhancement in both surface exchange and bulk diffusion kinetics. Specifically, materials with the nominal composition of Ba(Co0.4 Fe0.4 Zr0.1 Y0.1 )0.975 O3− δ and Ba(Co0.4 Fe0.4 Zr0.1 Y0.1 )0.95 O3− δ show significantly improved activity for ORR at reduced temperatures with the area specific resistances of 0.011 and 0.024 Ω cm 2 at 600 °C, as a comparison of 0.042 Ω cm 2 for the cation stoichiometric BCFZY. Excessive B‐site deficiencies, however, lead to the formation of impurity phases, which cause a block for charge transfer and, consequently, a reduction in electrode performance. Introducing a B‐site cation deficiency is a promising way to optimize the activity of perovskite oxides for ORR at reduced temperatures, but the degree of deficiency shall be carefully tuned. Abstract : The oxygen reduction activity of BaCo0.4 Fe0.4 Zr0.1 Y0.1 O3– δ can be boosted via introducing a slight B‐site cation deficiency (2.5 or 5 at%), and such an improvement is assigned to an increase in oxygen mobility bringing enhancement in both surface exchange and bulk diffusion kinetics. Introducing a B‐site cation deficiency is a promising way to optimize the activity of cathodes at reduced temperatures.